2022
DOI: 10.1038/s41467-022-32743-w
|View full text |Cite
|
Sign up to set email alerts
|

Multi-pathway DNA-repair reporters reveal competition between end-joining, single-strand annealing and homologous recombination at Cas9-induced DNA double-strand breaks

Abstract: DNA double-strand breaks (DSB) are repaired by multiple distinct pathways, with outcomes ranging from error-free repair to mutagenesis and genomic loss. DSB-repair pathway cross-talk and compensation is incompletely understood, despite its importance for genomic stability, oncogenesis, and genome editing using CRISPR/Cas9. To address this, we constructed and validated three fluorescent Cas9-based reporters, named DSB-Spectrum, that simultaneously quantify the contribution of multiple DNA repair pathways at a D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 64 publications
2
37
0
Order By: Relevance
“…In contrast, depletion of these proteins had differential effects on SSA activity (Figure 6D right panel, Supplemental figure 3E). BRCA1 depletion resulted in a decrease in SSA, whereas BRCA2 depletion resulted in an increase in SSA usage, consistent with previous publications (Anantha et al, 2017; Stark et al, 2004; van de Kooij et al, 2022). Importantly, whereas cells lacking both EXO1 and BRCA1 had substantially reduced levels of SSA, concomitant loss of EXO1 did not affect the level of SSA in BRCA2-depleted cells (Figure 6D).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…In contrast, depletion of these proteins had differential effects on SSA activity (Figure 6D right panel, Supplemental figure 3E). BRCA1 depletion resulted in a decrease in SSA, whereas BRCA2 depletion resulted in an increase in SSA usage, consistent with previous publications (Anantha et al, 2017; Stark et al, 2004; van de Kooij et al, 2022). Importantly, whereas cells lacking both EXO1 and BRCA1 had substantially reduced levels of SSA, concomitant loss of EXO1 did not affect the level of SSA in BRCA2-depleted cells (Figure 6D).…”
Section: Resultssupporting
confidence: 92%
“…We thereafter considered that BRCA1-deficient cells depend on the function of EXO1 in long-range end-resection during DSB repair. Using our newly developed multi-pathway reporter for DSB repair, we recently found that long-range end-resection mediated by EXO1 is not required for HR but promotes SSA (van de Kooij et al, 2022). To substantiate these findings in a BRCA1-deficient setting, we examined ionising irradiation-induced foci (IRIF) of RAD51 and RAD52 in our BRCA1-deficient cell lines as a read-out of HR and SSA, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations